Improvements to the Electric Cane Cutter by Design and Simulation - Suhaimi, Nur Ayunie; Mohd Rahim, Rida Zahirah; Rustam, Muhammad Zharfan; Yahya, Ts. Mohd Shahir (Multidisciplinary Applied Research and Innovation, 2022)
The ECC project is aimed at small-scale local sugarcane farmers who can’t afford the high expense of hiring staff or advanced cutting gear. As a result, the ECC’s main goal is to assist small-scale local sugarcane farmers in reducing staff and sugarcane production time while also producing high-quality sugarcane in large quantities.This project’s concept was once again developed, leading to the development of a new idea for combining cutting and packing simultaneously pace. The concept, gravitational force had been used to create this machine, and it evolved in this idea. This function focuses on gravity to control the movement of the cane during cutting without the need for human interference.The Electric Cane Cutter project’s prototype production includes secure materials such as alloy, High Density Polyethylene, Mild Steel, Motor, and Saw Blade (for cutting sugarcane). Cutting, joining, welding, and bending are all parts of the fabrication process for this prototype. We also use Solidworks 2020 software to design the final prototype, and solidworks simulation analysis to demonstrate the prototype’s strength and durability. Upon conducting various tests on ECC with a maximum input of 4 sugarcanes, the estimated new cutting and packaging productivity improved to 24 packets per hour. The increase in productivity has been approximately 100 % . In a summary, it is hoped that this project would aid small-scale local sugarcane farmers to produce a large amount of sugarcane at a low cost. It is hoped that the project’s output would help small-scale local sugarcane farmers boost their productivity even further.